Античная литература. Рим: хрестоматия / сост.: Н. А. Федоров, В. А. Мирошенкова - Федоров Николай Алексеевич (Высшая школа, 1999)
Экземпляры: ф. 3 (20131209) / Инвентарный номер: 32053 / Цена: 57.00 / Авт.знак: А 72 / ГРНТИ: 17.82 / ББК: 84(0)35я73